The Influence Of Superleadership, Work Engagement, And Job Crafting, On Turnover Intention In Millennial Employees - Suwandi, Suwandi; Nababan, Lasma Debora (DPPM Universitas Pelita Bangsa, 2023)
Human resources as an important investment for many companies, the development of a company, various problems arise related to human resources. One of the serious problems that exist in human resources is employee turnover intention behaviour. The purpose of this study is to determine whether Superleadership negatively affects turnover intention in millennial employees of PT Merobi Artha Putera, to determine whether Work Engagament negatively affects turnover intention in millennial employees of PT Merobi Artha Putera, and to determine whether Job Crafting negatively affects turnover intention in millennial employees of PT Merobi Artha Putera. The method used in this research is quantitative method, examining the population or sample, namely millennial generation employees of PT Merobi Artha Putera. data collection using research instruments, data analysis is quantitative / statistical, with the aim of testing predetermined hypotheses. The independent variables in this study are, Superleadership (X1), Work engagement (X2) and Job crafting (X3). And the dependent variable in this study is turnover intention (Y). The findings of this study are that: 1) Superleadership has a negative and significant effect on turnover intention in millennial employees of PT Merobi Artha Putera. 2) Work engagement has a positive and significant effect on turnover intention in millennial employees of PT Merobi Artha Putera. 3) Job crafting has no effect on turnover intention in millennial employees of PT Merobi Artha.